A theory of tolerance - Giacomo Corneo; Olivier Jeanne (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
We develop an economic theory of tolerance where endogenous lifestyles and exogenous traits are invested with symbolic value by people. Value systems are rationally chosen by parents for their children. In conjunction with actual behavior, value systems determine the esteem enjoyed by individuals. Intolerant individuals attach all symbolic value to a small number of attributes and are irrespectful of people with dierent ones. Tolerant people have diversified values and respect social alterity. We study the formation of values attached to various types of attributes and identify circumstances under which tolerance spontaneously arises. Policy may aect the evolution of tolerance in distinctive ways, and there may be efficiency as well as equity reasons to promote tolerance.
Keywords: D1; O1; 330; value systems; tolerance; Kinder; Gesellschaftliches Bewusstsein; Risiko; Verhalten; Eltern